The Impact of Job Automation On Workers In Indonesia’s Garment Companies - Ariyani, Luthfina; Indraprahasta, Galuh Syahbana; Pitaloka, Ardanareswari Ayu (STI Policy and Management Journal, 2024)
JJob automation through the adoption of more advanced technologies under the fourth industrial revolution (Industry 4.0) has significantly impacted many countries, including Indonesia. In particular, the abundance of Indonesia’s human resources, given the country’s demographic bonus, is challenged by the skills of workers. In this study, our departure is the potential conflict of the human-technology nexus in Indonesia’s garment industry, a labor-intensive line of industry. The objectives of this study are twofold. First, it aims to dissect the multi-level factors in the adoption of Industry 4.0 technology in Indonesia’s garment industry. Second, it aims to understand the impact of job automation on labor-intensive workers in Indonesia’s garment industry. Based on a number of semi-structured interviews supported by relevant secondary data, this study reveals that multi-level factors do affect the adoption of Industry 4.0 technology and its entailing shift in workers’ utilization in Indonesia’s garment industry. Instead of replacing workers, Indonesia’s garment companies tend to utilize technology as a complementary element. However, there is a need to shift the state of industrial workers, in terms of their mindset and skills    Keywords: Job Automation, Garment Industry, Labour Intensive, Indonesia